Digitalisation factors influencing the dynamic capabilities of small and medium enterprises in the healthcare sector - P. Makelana; R. Kekwaletswe; M. A. Segooa (International Journal of Science Annals)
Background and Aim of Study: Digitalization is problematized as one of the ways to improve dynamic capabilities of healthcare sector small and medium enterprises (SMEs) in their strive to stay competitive in today’s digital society. Digitalisation and dynamic capability are current key issues in both academia and practice due to the recent advances in information and communication technologies. Nonetheless, there is inadequate research informing what and why digitalisation can be leveraged to enhance the dynamic capabilities (DC), in the context of SMEs in healthcare sector. The aim of the study: to explore and explain factors influencing DC of healthcare SMEs in South Africa. Material and Methods: The study employed task-technology fit theory as a lens to explain digitalisation factors influencing the DC of SMEs. To achieve the aim of the study, a deductive approach was followed. The study population was healthcare sector SMEs, in South Africa. The sampling frame was 384 randomly selected SMEs, in a self-administered survey. Results: The empirical results show that SME performance (β=0.132, p<0.05), task-technology fit (β=0.052, p<0.05), internet access (β=0.235, p<0.05), customer service (β=0.057, p<0.05), information sharing (β=0.022, p<0.05), innovation (β=0.125, p<0.05), and data security (β=0.427, p<0.05) are highly significant in the digitalisation of DC of SMEs. While cost saving (β=0.178, p>0.05) was found to be less significant. Conclusions: The study has explained and shown that appropriating technology to task during digitalisation is key to enhancing dynamic capabilities, in the context of South African healthcare sector SMEs. The cost of digital technology is a none factor. Subsequently, digitalization is a people-driven transformation journey.